3D‐T1ρ prepared zero echo time‐based PETRA sequence for in vivo biexponential relaxation mapping of semisolid short‐T2 tissues at 3 T. Issue 4 (28th January 2019) - Sharafi, Azadeh; Baboli, Rahman; Chang, Gregory; Regatte, Ravinder R.
Abstract : Background: In addition to the articular cartilage, osteoarthritis (OA) affects several other tissues such as tendons, ligaments, and subchondral bone. T1ρ relaxation study of these short T2 tissues may provide a more comprehensive evaluation of OA. Purpose: To develop a 3D spin‐lattice relaxation in the rotating frame (T1ρ ) prepared zero echo time (ZTE)‐based pointwise encoding time reduction with radial acquisition (3D‐T1ρ ‐PETRA) sequence for relaxation mapping of semisolid short‐T2 tissues on a clinical 3 T scanner. Study Type: Prospective. Population: Phantom, two bovine whole knee joint and Achilles tendon specimens, 10 healthy volunteers with no known inflammation, trauma or pain in the knee or ankle. Field Strength/Sequence: A customized PETRA sequence to acquire fat‐suppressed 3D T1ρ ‐weighted images tissues with semisolid short T2 / T 2 * relaxation times in the knee and ankle joints at 3 T. Assessment: Mono‐ and biexponential T1ρ relaxation components were assessed in the patellar tendon (PT), anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), and Achilles tendon (AT). Statistical Tests: Kruskal–Wallis with post‐hoc Dunn's test for multiple pairwise comparisons. Results: Phantom and ex vivo studies showed the feasibility of T1ρ relaxation mapping using the proposed 3D‐T1ρ ‐PETRA sequence. The in vivo study demonstrated an averaged mono‐T1ρ relaxation of (median [IQR]) 15.9 [14.5] msec, 23.6 [9.4] msec, 17.4 [7.4] msec, and 5.8 [10.2] msec in the PT, ACL, PCL, and AT, respectively. The bicomponent analysis showed the short and long components (with their relative fractions) of 0.65 [1.0] msec (46.9 [15.3]%) and 37.3 [18.4] msec (53.1 [15.3]%) for PT, 1.7 [2.1] msec (42.5 [12.5]%) and 43.7 [17.8] msec (57.5 [12.5]%) for ACL, and 1.2 [1.9] msec (42.6 [14.0]%) and 27.7 [14.7] msec (57.3 [14.0]%) for PCL and 0.4 [0.02] msec (58.8 [13.3]%/) and 31.3 [10.8] msec (41.2 [13.3]%) for AT. Statistically significant ( P ≤ 0.05) differences were observed in the mono‐ and biexponential relaxation between several regions. Data Conclusion: The 3D‐T1ρ ‐PETRA sequence allows volumetric, isotropic (0.78 × 0.78 × 0.78 mm), biexponential T1ρ assessment with corresponding fractions of the tissues with semisolid short T2 / T 2 * . Level of Evidence: 2 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2019;50:1207–1218.